The macroeconomic impact of defense expenditure on economic growth of Pakistan: An econometric approach - Haseeb, Muhammad; Abu Bakar, Nor'Aznin; Azam, Muhammad; Hassan, Sallahuddin; Hartani, Nira Hariyatie (Canadian Center of Science and Education, 2014)
The broad objective of the present study is to examine whether a long run relationship between defense expenditure and economic growth of Pakistan exist.For empirical investigation, an annual time series data over the period from 1980-2013, and ARDL was used.The empirical results support the existence of long run negative relationship between defense expenditure and economic growth.The results for long run negative relationship between defense expenditure and economic growth was suggested just in case Pakistan MKH does not hold during the period under study.The findings further suggested that the policy makers need to formulate appropriate policy to encourage and not to discourage the economic growth and development of Pakistan